[LB.02.28] HIGH PROTEIN INTERMITTENT FASTING INCREASES SERUM POLYCHLORINATED BIPHENYLS AND DECREASES OXIDATIVE STRESS IN OBESE ADULTS. (September 2017) - He, F.; Zuo, L.; Emery, W.; Arciero, P.
Abstract : Objective: The purpose of this study is to exam the effect of 12-week high-protein intermittent fasting and 52-week of modified high-protein caloric restriction on serum polychlorinated biphenyls (PCBS) and oxidative stress in 40 obese men and females. Design and method: Forty obese adults (men, n = 21; women, n = 19) were recruited. Study was divided into two separated phases (Phase I and Phase II). Phase I: 12-week high-protein, intermittent fasting, low-calorie weight loss diet. Phase II: 52-week weight maintenance diet comparing high-protein, intermittent fasting with a traditional heart healthy diet. Serum polychlorinated biphenyls and oxidative stress biomarkers (e.g., thiobarbituric acid reactive substances, TBARS; total antioxidant capacity, TAC) were measured at weeks 1 (baseline), 12 (end of Phase I), and 64 (end of Phase II). Results: Following 12-week acute weight loss stage (Phase I) TBARS was reduced compared to the baseline (0.24 ± 0.15 vs. 0.18 ± 0.11 μM; p < 0.01), which was accompanied by the increase in TAC (18.9 ± 2.6 vs. 19.9 ± 2.3 nmol/mL; p < 0.02). PCB serum concentrations were significantly increased (86.7 ± 45.6 vs. 115.6 ± 65.9 ng/g lipid; p < 0.01). However, there was no significant difference between women and men. Following 52-week of weight maintenance stage (Phase II), two individual PCBs (PCB 170 and PCB 180) were significantly higher in modified high-protein caloric restriction diet compared to the traditional heart healthy diet. Additionally, PCB changes were positively correlated with TBARS levels (r > 0.42, p < 0.05) and negatively correlated with body composition changes. Conclusions: In conclusion, a 12-week high-protein intermittent fasting diet effectively induced weight loss, mobilized stored PCBs by increasing circulating level of PCBs as well as favorably altered redox status. Moreover, 52-week modified high-protein caloric restriction diet demonstrated an advantage in preventing weight relapse in the absence of elevated oxidative stress induced by increased PCBs compared to traditional heart heathy diet.